2012
DOI: 10.5324/nje.v22i2.1568
|View full text |Cite
|
Sign up to set email alerts
|

The association between vascular factors and subjective memory impairment in older people: The HUNT Study, Norway

Abstract: Objectives: Subjective memory impairment (SMI) is often considered an early sign of dementia. This study investigates the relationship between SMI and dementia-related vascular factors in older people. Method: This study was based on data from 12,255 individuals, 65 years and older, participating in the Nord-Trøndelag health study, third survey 2006-08 (HUNT3). SMI, vascular diseases, exercise, smoking, and alcohol consumption were self-reported. Blood pressure, cholesterol and body mass index (BMI) were clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
0
6
1
1
Order By: Relevance
“…However, including cardiovascular related variables into the linear regression model in the present data set did not change the gender association with the SMI sum score substantially. In a previous paper from the same HUNT population it was demonstrated a clear associations between stroke and heart disease and higher levels of SMI, otherwise strong positive relationships between cardiovascular risk factors and SMI were not found (Langballe et al 2012). As a conclusion, there is no evidence in our data that the different cardiovascular risk can explain the gender differences in SMI.…”
Section: Discussioncontrasting
confidence: 82%
“…However, including cardiovascular related variables into the linear regression model in the present data set did not change the gender association with the SMI sum score substantially. In a previous paper from the same HUNT population it was demonstrated a clear associations between stroke and heart disease and higher levels of SMI, otherwise strong positive relationships between cardiovascular risk factors and SMI were not found (Langballe et al 2012). As a conclusion, there is no evidence in our data that the different cardiovascular risk can explain the gender differences in SMI.…”
Section: Discussioncontrasting
confidence: 82%
“…In line with our results, Scuteri et al previously reported that hypotensive episodes (defined as at least one reading <100 mmHg) during 24‐h ambulatory monitoring—which could plausibly have resulted from daytime orthostatic fluctuations—were more common in those with SMI (Scuteri et al ., ). The HUNT study, which sampled a population of 12 225 participants, aged 65 and over, found that relative to moderate sitting SBP levels, higher seated SBP was associated with better subjective memory—in line with our results suggesting that lower supine BP drives lower SBP following orthostatic stress (Langballe et al ., ). Lower OBP, even at sub‐clinical levels, may not be effectively compensated by auto‐regulatory processes, and this may result in inadequate hemodynamic responses to cognitive demands (Tzeng and Ainslie, ).…”
Section: Discussionmentioning
confidence: 97%
“…Although sex differences in cognitive deficits remain poorly understood (Mielke et al ., ), a recent study has suggested that SMI may reflect objective cognition in men but affective state in women (Tomita et al ., ); women reported poorer subjective memory despite having better objective cognition; men, however, were more accurate in self‐appraisal of cognitive abilities. The HUNT study also described sex differences in their findings—in men, but not in women, lower seated systolic BP was related to greater SMI relative to moderate seated systolic BP (Langballe et al ., ). Interestingly, older men have previously been shown to have higher rates of OH‐related hospitalisations and demonstrate poorer cerebral auto‐regulation during standing than women (Deegan et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Another problem with assessing SMI is that the relationship between self-reported memory impairment and performance-based measures of memory is far from clear, as both positive 4 5 7–10 and negative associations have been obtained. 11 However, there are many indications that SMI is related to depression 9 12 ; personality traits such as neuroticism 13 14 ; vascular factors such as heart disease and stroke 15 16 ; brain changes such as white matter hyperintensities, 17 brain metabolic dysfunction 18 and structural changes 19–21 ; and psychosocial stress. 16 Research on the relationship between SMI and development of Alzheimer’s disease (AD) and dementia has demonstrated mixed results, both positive 22–24 and negative associations.…”
Section: Introductionmentioning
confidence: 99%